General methods for studying input material flows of conveyor transport system - Pihnastyi, O. M.; Sobol, Maksym (Odesa National Maritime Academy, 2023)
A transport system model based on neural network can be used in the synthesis of algorithms for optimal control of a conveyor section flow parameters, in order to reduce the specific energy consumption of material transportation.

Модель транспортної системи на основі нейронної мережі може бути використана при синтезі алгоритмів оптимального керування параметрами потоку секції конвеєра з метою зниження питомих енерговитрат на транспортування матеріалу.
Загальні методи дослідження вхідних матеріальних потоків конвеєрно-транспортної системи
Keywords: neural network; conveyor section; нейроннa мережa; поток секції конвеєра